MENINGKATKAN KEMAMPUAN MENGENAL BILANGAN MELALUI METODE MULTISENSORI BAGI ANAK AUTIS - Yeni - Evri (Jurnal Penelitian Pendidikan Khusus, 2012)
This research coming because of there is a problem in the First Grade Class in Autism Harapan Bunda Padang School. While, in this place there is two autism kids and one teacher. The teacher cannot teach well especially  when he teach about numbers. In this case teacher still using conventional method and techniques such as lectures, demonstration class, giving assignment and multisensory which is not optimally. This research aims to describe the learning process troght the number 1-10 with multisensory method and also in proving the effectiveness of using multisensory method to improve the ability to recognize the numbers in autism children.